Matrix Metalloproteinase-3 Down Regulation and Cell Migration Inhibition in Human Pterygium Fibroblasts by Mitomycin-C, Curcumin and Fibrin Glue - Ferdian Ramadhan; Jamaluddin Jamaluddin; Ismi Zuhria; Luki Indriaswati; Evelyn Komaratih (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Pterygium is an ocular surface disease that often occurs in tropical countries with a high recurrence rate. Matrix metalloproteinase-3 (MMP-3) play a key role in the inflammatory process of pterygium. This study aims to investigate the ability of curcumin and fibrin glue (FG) in suppressing the expression of MMP-3, and whether can be expected as adjuvant therapy to reduce pterygium recurrence.METHODS: Human pterygium fibroblasts (HPF) obtained from primary cultured of pterygium were treated with no treatment, curcumin, mitomycin-C (MMC), and FG. MMP-3 expression was analyzed using immunocytochemistry and the intensity measurement was done using ImageJ software. Cell migration was measured by scratching and stratification of fibroblast culture after cell confluence, and assessed for 48 hours.RESULTS: The expression of MMP-3 were lower in the HPF treated with 100 mol/mL curcumin, 200 mol/mL, and FG (2205.84±86.1 pg/mL, 1002.51±25.22 pg/mL, 1131.55±17.71 pg/mL, respectively) in comparison with untreated HPF (4703.49±108.9 pg/mL). The expression of MMP-3 were significantly different between groups (p<0.001). Cell migration of HPF after scratching with curcumin intervention at 200 mol/mL decrease from 178.67±2.85 (24 hours) to 88.83±1.48 (48 hours). Meanwhile the migration in FG group also decrease from 180.4±2.56 (24 hours) to 72.45±1.25 (48 hours).CONCLUSION: Curcumin and FG able to reduce the expression of MMP-3 and inhibit the migration of HPF cells.KEYWORDS: curcumin, mitomycin C, fibrin glue, human pterygium fibroblast, MMP-3